The Black Panther Party : service to the people programs - Hilliard, David (University of New Mexico Press, 2008)
"The Black Panther Party represents Party members' coordinated responses to the failure of city, state, and federal bureaucrats to address the basic needs of their respective communities. The Black Panther Party pioneered free social service programs that are now in the mainstream of American life." "The Black Panther Party's Sickle-Cell Anemia Research Foundation, operated with Oakland's Children's Hospital, was among the nation's first such testing programs. It's Free Breakfast Program served as a model for national programs. Other initiatives included free clinics, grocery giveaways, school and education programs, senior programs, and legal aid programs."